Clean Style Recovery and Utilization of Residual Nutrients in Effluents From Biohydrogen Production: In Situ Immobilization Based on Sodium Alginate - Ai, Fuke; Zhang, Yang; Fan, Xiaoni; Li, Yameng; Zhang, Haorui; Jiao, Yinggang; Zhang, Quanguo; Yong, Cheng; Zhao, Jinfei; Petracchini, Francesco; Paolini, Valerio; Zhang, Zhiping (Frontiers in Bioengineering and Biotechnology, 2022)
Clean and high value recovery and reuse of the residue of biohydrogen production (biohydrogen slurry) is an urgent problem to be solved. In this paper, the sodium alginate (SA) gel was used to concentrate nutrients quickly in-situ from biohydrogen slurry, which was prepared into gel microspheres (GM), just like “capsule”. The immobilization and release efficiency of conventional and reverse spherification were investigated. Better immobilization and release efficiency were detected under conventional spherification method. The effect of GM sizes, concentrations of SA and calcium chloride (CaCl2) were further studied in terms of Sphericity Factor, nutrients release, yield, encapsulation efficiency and loading capacity. The best immobilization effect was obtained with 1.6 mm syringe needle, 3.0 wt%SA, and 6 wt% CaCl2, in which the Sphericity Factor, nitrogen release, yield, nitrogen encapsulation efficiency and nitrogen loading capacity reached to 0.047, 96.20%, 77.68%, 38.37% and 0.0476%, respectively. This process not only avoids environmental pollution from biohydrogen slurry, but also uses them at a high value as fertilizer to nourish the soil. The feasibility of “slurry capsule” preparation will realize the clean recovery and reuse of biohydrogen slurry, which provides a new idea for ecological protection and carbon neutral goals, and has important significance for sustainable development.